PKHB1 Tumor Cell Lysate Induces Antitumor Immune System Stimulation and Tumor Regression in Syngeneic Mice with Tumoral T Lymphoblasts. (4th June 2019) - Martínez-Torres, Ana Carolina; Calvillo-Rodríguez, Kenny Misael; Uscanga-Palomeque, Ashanti Concepción; Gómez-Morales, Luis; Mendoza-Reveles, Rodolfo; Caballero-Hernández, Diana; Karoyan, Philippe; Rodríguez-Padilla, Cristina
Abstract : Acute lymphocytic leukemia (ALL) is the most common pediatric cancer. Currently, treatment options for patients with relapsed and refractory ALL mostly rely on immunotherapies. However, hematological cancers are commonly associated with a low immunogenicity and immune tolerance, which may contribute to leukemia relapse and the difficulties associated with the development of effective immunotherapies against this disease. We recently demonstrated that PKHB1, a TSP1-derived CD47 agonist peptide, induces immunogenic cell death (ICD) in T cell ALL (T-ALL). Cell death induced by PKHB1 on T-ALL cell lines and their homologous murine, L5178Y-R (T-murine tumor lymphoblast cell line), induced damage-associated molecular patterns (DAMPs) exposure and release. Additionally, a prophylactic vaccination with PKHB1-treated L5178Y-R cells prevented tumor establishment in vivo in all the cases. Due to the immunogenic potential of PKHB1-treated cells, in this study we assessed their ability to induce antitumor immune responses ex vivo and in vivo in an established tumor. We first confirmed the selectivity of cell death induced by PKBH1 in tumor L5178Y-R cells and observed that calreticulin exposure increased when cell death increased. Then, we found that the tumor cell lysate (TCL) obtained from PKHB1-treated L5178YR tumor cells (PKHB1-TCL) was able to induce, ex vivo, dendritic cells maturation, cytokine production, and T cell antitumor responses. Finally, our results show that in vivo, PKHB1-TCL treatment induces tumor regression in syngeneic mice transplanted with L5178Y-R cells, increasing their overall survival and protecting them from further tumor establishment after tumor rechallenge. Altogether our results highlight the immunogenicity of the cell death induced by PKHB1 activation of CD47 as a potential therapeutic tool to overcome the low immunogenicity and immune tolerance in T-ALL.